2004
DOI: 10.1016/j.femsle.2004.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Quinate oxidation inGluconobacter oxydansIFO3244: purification and characterization of quinoprotein quinate dehydrogenase

Abstract: Quinoprotein quinate dehydrogenase (QDH) is a membrane-bound enzyme containing pyrroloquinoline quinone (PQQ) as the prosthetic group. QDH in Gluconobacter oxydans IFO3244 was found to be inducible by quinate and it is not constitutively expressed in the absence of quinate. The purification of holo-form of QDH to nearly homogeneity was achieved. The purified QDH appears to have two subunits of approximately 65 and 21 kDa, which could be the result of proteolysis of single polypeptide. Kinetic analysis indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the last decade, a variety of other PQQ-dependent dehydrogenase activities were purified from acetic acid bacteria. Among them are enzymes that oxidize quinate [Vangnai et al, 2004], meso -erythritol [Moonmangmee et al, 2002b], cyclic alcohols [Moonmangmee et al, 2001], and D -arabitol [Adachi et al, 2001a]. Unfortunately, we cannot identify the corresponding genes in the genome, as the genes encoding these proteins have not been characterized, but Matsushita et al [2003] showed that the PQQ-containing glycerol dehydrogenase ( sldAB ) is accountable for meso -erythritol and D -arabitol oxidation in G. oxydans strain IFO3257.…”
Section: Respiratory Chainmentioning
confidence: 99%
“…In the last decade, a variety of other PQQ-dependent dehydrogenase activities were purified from acetic acid bacteria. Among them are enzymes that oxidize quinate [Vangnai et al, 2004], meso -erythritol [Moonmangmee et al, 2002b], cyclic alcohols [Moonmangmee et al, 2001], and D -arabitol [Adachi et al, 2001a]. Unfortunately, we cannot identify the corresponding genes in the genome, as the genes encoding these proteins have not been characterized, but Matsushita et al [2003] showed that the PQQ-containing glycerol dehydrogenase ( sldAB ) is accountable for meso -erythritol and D -arabitol oxidation in G. oxydans strain IFO3257.…”
Section: Respiratory Chainmentioning
confidence: 99%
“…[4][5][6] In the cytoplasm, SKDH (EC 1.1.1.25) catalyzes a reversible reaction of SKA oxidation to 3-dehydroshikimate and 3-dehydroshikimate reduction to SKA. In the previous papers, we proposed SKA production by a single cellular system of acetic acid bacteria, 4,5,7,8) but many times of trial and error combining the two separately localized enzymatic systems taking place outside and inside the cells together have given insufficient production of SKA.…”
mentioning
confidence: 99%
“…However, the NADP-dependent ArDH from G. oxydans CGMCC 1.110 could efficiently oxidize some polyols to ketoses ( Table 2). The membrane-bound and PQQ-dependent polyol dehydrogenases purified from Gluconobacter species belonged to the long-chain dehydrogenase with a molecular mass of more than 80 kDa [9,23,25], and some had at least two subunits [9,23,26]. On the contrary, ArDH from G. oxydans CGMCC 1.110 belonged to the short-chain dehydrogenase just with a molecular mass of 29 kDa.…”
Section: Substrate and Cosubstrate Specificity Of Ardhmentioning
confidence: 96%
“…These membrane-bound enzymes contained pyrroloquinoline quinone (PQQ) as the prosthetic group and Ca 2+ was the preferred divalent metal. The membrane-bound and PQQ-dependent polyol dehydrogenases purified from Gluconobacter species belonged to the long-chain dehydrogenase with a molecular mass of more than 80 kDa [9,23,25], and some had at least two subunits [9,23,26]. The NAD(P)-dependent enzyme made no contribution to cyclic alcohol oxidation but contributed to the reduction of cyclic ketones to cyclic alcohols [24].…”
Section: Substrate and Cosubstrate Specificity Of Ardhmentioning
confidence: 99%